Activation through sport as a way of social inclusion and integration of people with disabilities - Niedbalski, Jakub (Acta Universitatis Lodziensis. Folia Sociologica, 2016)
Purpose of the article is to demonstrate the manner, in which the concept of social integration of the disabled, where crucial place is occupied by sports activity, is realized on the background of social and institutional conditions. There are qualitative data used in the research, collected through a technique of an in-depth free interview and observations, conducted among the disabled who play sports. Analysis and interpretation of the empirical material and existing data is performed in accordance with principles of the grounded theory. The performed studies proved that sport practiced by the disabled may support the inclusion process of the disabled into broader social circles. Sport not only an opportunity to maintain fitness and health, but also for social integration of the disabled.